The smaller bowel: imaging the small bowel in paediatric Crohn's disease. Issue 1026 (17th January 2011) - Stuart, Sam; Conner, Thomas; Ahmed, Asia; Steward, Michael; Maclachlan, Jody; Wylie, Peter; Beal, Isobel
Abstract : Crohn's disease begins in childhood in 20% of cases. Imaging of the small bowel is needed for diagnosis and management and also to inform the clinician of the location, extent, and activity of disease. There are several modalities available to image the small bowel and the combined use of these is often required to optimise benefit. Methods available for imaging the small bowel include barium studies, sonography, CT, wireless capsule endoscopy, nuclear medicine studies, and MRI. Patient comfort is paramount in imaging paediatric patients. Therefore, non-invasive techniques are most likely to be successful. Furthermore, as children are at greatest risk of radiation induced malignancy, modalities which do not carry a radiation burden are preferable. This article discusses the methods available for imaging the small bowel in paediatric Crohn's disease and the relative merits of each modality.